Implementation of spectral difference method on overset grids for compressible inviscid flows. (25th November 2016) - Yang, Liu; Yang, Aiming
Highlights: An effective chimera technique for spectral difference method was proposed. The interpolation scheme is compact and high-order accurate. The method was applied to simulate the flow around a hovering rotor. Abstract: This work investigates the use of a high-order spectral difference (SD) method on overset grids for the solution of the Euler equations. A spectral difference method of up to fourth order for hexahedral elements is employed as the spatial discretization scheme and the explicit four-stage Runge–Kutta method is utilized for time integration. In order to preserve the high-order accuracy throughout the whole computation domain, an interpolation method for overlapping interfaces is developed. To validate this interpolation method and the accuracy of the overall algorithm, the inviscid convection of a vortex and subsonic flow over a wing are calculated. Then the flow over a hovering rotor is simulated by the high-order SD method on overset grids. The numerical results demonstrated the capability and accuracy of the present algorithm on overset grids.